Daring to care : American nursing and second-wave feminism - Malka, Susan Gelfand (Urbana : University of Illinois Press, 2007)
Arguing that feminism helped to end nursing's subordination to medicine and provided nurses with greater autonomy and professional status, the author examines the impact of second-wave feminism on the nursing field since the 1960s.
List of figures -- Acknowledgments -- List of abbreviations -- Introduction -- pt. 1. Nursing in the postwar period -- 1. Hospitals, hierarchies, and the duty to care -- 2. Nursing education in the age of the apron -- 3. Reforming and liberating nursing education -- pt. 2. Nursing and equality feminism -- 4. Nursing education and the end of the apron -- 5. Nursing work, culture, and identity -- pt. 3. Nursing in the era of difference feminism -- 6. Nursing and the feminist enlightenment -- 7. New pathways for nurses -- Epilogue : A more inclusive history -- Notes -- Index.
Includes bibliographical references (pages 171-211) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: Nursing -- United States -- History; Feminism -- United States -- History; Nurses -- United States -- Social conditions; History of Nursing; Education, Nursing -- history; Feminism -- history; History, 20th Century; Women's Rights -- history; United States; Féminisme -- États-Unis -- Histoire; Infirmières -- États-Unis -- Conditions sociales; Médecine -- Histoire -- 20e siècle.; SOCIAL SCIENCE / General; Feminism; Nurses -- Social conditions; Nursing; United States; Berufsausbildung; Krankenpflege; Frauenbewegung; Feminismus; USA; History